Juridical Study on Cooperative Legal Entity Bankruptcy Submissions by Its Member - Adis Nur Hayati (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The Covid-19 pandemic resulted in several cooperatives failing to pay and made many of their members file bankruptcy petitions against their cooperatives, this condition then caused opposition from several parties. Therefore, this paper aims to examine the issue of filing for bankruptcy of a cooperative legal entity by its member with questions: 1) how is the legal construction of Indonesian cooperative bankruptcy, 2) whether the permissibility of filing a bankruptcy petition against cooperatives by its member is in line with the characteristics of Indonesian cooperative legal entities. The method used is normative juridical research. The results show 1) Law no. 37 of 2004 and Law no. 25 of 1992 do not regulate restrictions on legal subjects who can file for bankruptcy against cooperatives. Therefore, the cooperative itself, members of the cooperative, and other creditors have the right to file for bankruptcy against the cooperative. 2) The filing of a petition for bankruptcy of a cooperative by its member (who is a creditor) is not in accordance with the characteristics of Indonesian cooperatives, considering that each of cooperative members is the owners of the cooperative itself and the main basis for the operation of cooperatives is the principles of kinship and democracy. Thus, it is concluded that the filing of a petition for bankruptcy of a cooperative by its member (who has a position as a creditor) is valid but is not in accordance with the characteristics of the legal entity of Indonesian cooperatives. Therefore, the government is advised to review the terms and restrictions on legal subjects who can petition for bankruptcy against cooperatives.